2014
DOI: 10.1242/jcs.130518
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of glypican-1 by intronic microRNA-149 fine-tunes the angiogenic response to fibroblast growth factor in human endothelial cells

Abstract: MicroRNA-149 (miR-149) is located within the first intron of the glypican-1 (GPC1) gene. GPC1 is a low affinity receptor for fibroblast growth factor (FGF2) that enhances FGF2 binding to its receptor (FGFR1), subsequently promoting FGF2-FGFR1 activation and signaling. Using bioinformatic approaches, both GPC1 and FGFR1 were identified and subsequently validated as targets for miR-149 (both the mature strand, miR-149, and the passenger strand, miR-149*) in endothelial cells (ECs). As a consequence of their targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 58 publications
(98 reference statements)
2
38
0
Order By: Relevance
“…miR-181a was expressed in endothelial cells and regulates Prox1, resulting in rapid and efficient transcript degradation and translational inhibition [29]. miR27a/b, miR-149 and miR-125A-5P were also reported to be associated to function of ECs [30][31][32]. These miRNAs abovementioned were up-regulated in hiPSC-ECs and hESC-ECs in our study.…”
Section: Similar and Different Mirna Expression In Hesc-ecs And Hipscsupporting
confidence: 57%
“…miR-181a was expressed in endothelial cells and regulates Prox1, resulting in rapid and efficient transcript degradation and translational inhibition [29]. miR27a/b, miR-149 and miR-125A-5P were also reported to be associated to function of ECs [30][31][32]. These miRNAs abovementioned were up-regulated in hiPSC-ECs and hESC-ECs in our study.…”
Section: Similar and Different Mirna Expression In Hesc-ecs And Hipscsupporting
confidence: 57%
“…A functional overlap of CS and HS for VEGF-induced angiogenesis has been previously discussed (Le Jan et al, 2012). Recently, the small non-coding microRNA149 has been linked to a new fine-tuning element of Fgf2-induced proliferation in endothelial cells by regulating the HS proteoglycan glypican (Chamorro-Jorganes et al, 2014). We have previously shown that the lack of decorin in skin led to the reduction of Ust and an impaired cell morphology in a 3D environment (Nikolovska et al, 2014;Jungmann et al, 2012), which could partially contribute to the delayed wound healing of the Dcn 2/2 mice (Järveläinen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid changes in endothelial cell proliferation rates occurs following activation of endothelium by angiogenic cytokines [2731,32,33 ■ ]. In fact, in the healthy adult, angiogenesis occurs only in select phases of the female reproductive cycle, to allow physiological adipose tissue expansion, as a protection mechanism in wound healing/tissue repair, and is almost exclusively associated with disorder when angiogenesis is induced by microenvironmental factors such as hypoxia or inflammation [3439].…”
Section: Regulation Of Vascular Development Growth and Differentiationmentioning
confidence: 99%
“…The relationship between miRNAs and their host gene is especially relevant in miRNAs encoded within an angiogenic host gene including miR-149 [32] and the highly conserved miR-218 is an intronic miRNA encoded within the Slit2 and Slit3 genes [5052]. Slits are secreted glycoproteins, which are the main ligands for roundabout receptors (Robos).…”
Section: Regulation Of Vascular Development Growth and Differentiationmentioning
confidence: 99%